2006
DOI: 10.1161/01.atv.0000239569.99126.37
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of Angiotensin II Receptors Reduces the Expression of Receptors for Advanced Glycation End Products in Human Endothelial Cells

Abstract: Objectives-Receptors for advanced glycation end products (RAGEs) play crucial roles in atherogenesis. Because tumor necrosis factor ␣ (TNF␣) is expressed and upregulates RAGE expression in atherosclerotic lesions, the TNF␣-RAGE interaction might be involved in the inflammatory process of atherogenesis. On the other hand, an angiotensin II type-1 receptor blocker (ARB), widely used as an antihypertensive drug, has been reported to have also antiatherosclerotic effects. Thus we investigated whether an ARB exerts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 16 publications
1
24
0
Order By: Relevance
“…In the present study, RAS blockade by temocaprilat and olmesartan, as well as DPI and NAC, markedly attenuated AGEtriggered RAGE expression, suggesting that both agents are capable of attenuating AGE-triggered RAGE activation. These findings are consistent with previous reports 36,42) and support the beneficial effects of ACEI and ARB in diabetic vascular complications.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, RAS blockade by temocaprilat and olmesartan, as well as DPI and NAC, markedly attenuated AGEtriggered RAGE expression, suggesting that both agents are capable of attenuating AGE-triggered RAGE activation. These findings are consistent with previous reports 36,42) and support the beneficial effects of ACEI and ARB in diabetic vascular complications.…”
Section: Discussionsupporting
confidence: 93%
“…Although such an effect on the AGE/RAGE axis has previously been observed in cell culture experiments [44] and postulated to be important in type 2 diabetic patients for plaque stabilisation [43], this is the first study to demonstrate effects of a statin on the AGE/RAGE pathway in diabetesaccelerated atherosclerosis. Indeed, our study suggests that statins may reduce AGE accumulation and thereby reduce activation of NAD(P)H oxidase, thus linking oxidant stress to altered gene expression via RAGE, as previously suggested in vitro and in gp91phox-deficient mice [45].…”
Section: Discussionmentioning
confidence: 63%
“…This up-regulation of the AGEs-RAGE axis activates NADPH oxidase with a resultant ROS generation (Wautier et al 2001) and atherosclerosis progression (Schmidt et al 1999). It has been reported that some ARBs (including OLM) (Fujita et al 2006) and nifedipine (a dihydropyridine CCB) reduce RAGE expression (Matsui et al 2009). Furthermore, it was recently reported that the combination therapy with OLM and AZL reduces ROS production via suppression of p22 phox and p47 phox expression and NADPH oxidase activity .…”
mentioning
confidence: 99%